Serum Magnesium Level of Newly Detected Patients with Glucose Intolerance and Its Comparison with Serum Magnesium Level of Age and Sex Matched Healthy Volunteers - Rahim, Muhammad Abdur; Mitra, Palash (Journal of Medicine, 2018)
Background: Hypomagnesaemia is associated with insulin resistance, diabetes mellitus (DM) and diabetic complications. Diabetic patients, on the other hand, often have low magnesium levels. This study was designed to evaluate serum magnesium level of patients with new diagnosis of any level of glucose intolerance e.g. impaired fasting glucose, impaired glucose tolerance (IGT) or DM and to compare these with serum magnesium level of age and sex matched healthy controls. Materials & Methods: This case-control study was done in out-patient department of BIRDEM General Hospital from July to September 2017. Newly detected patients with glucose intolerance (DM 49, IGT 1) were cases and equal number (50) of age and sex matched healthy volunteers were controls. Serum magnesium level was measures in all study participants and a comparison was made between cases and controls. Results: There was no significant difference between cases and controls regarding age (p=0.875), sex and body mass index (p=0.386). Serum magnesium level was normal in 29 cases and 37 controls and low in 21 cases and 13 controls. Mean serum magnesium was low in cases (0.70±0.14 m.mol/L) than controls (0.85±0.15 m.mol/L) but the difference was not significant (p=0.362). Serum magnesium level was negatively correlated with fasting blood glucose (r -0.526), 2-h post-glucose value (r -0.559) and glycated haemoglobin (r -0.551) among cases. Conclusion: Serum magnesium level was lower among patients with DM and IGT when compared with serum magnesium level of age and sex matched healthy volunteers and serum magnesium level was negatively correlated with glycaemic status. J MEDICINE JUL 2018; 19 (2) : 95-99